2009
DOI: 10.1021/jp905415v
|View full text |Cite
|
Sign up to set email alerts
|

Coupling CP-MD Simulations and X-ray Absorption Spectroscopy: Exploring the Structure of Oxaliplatin in Aqueous Solution

Abstract: A combined experimental-theoretical approach applying X-ray absorption spectroscopy and ab initio molecular dynamics (CP-MD) simulations is used to get insight into the structural determination of oxaliplatin, a third-generation anticancer drug of the cisplatin family, in aqueous solution. Experimental Pt L(III)-edge EXAFS and XANES spectra of oxaliplatin in water are compared with theoretical XAS spectra. The latter are obtained as statistically averaged spectra computed for a set of selected snapshots extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The remaining scattering paths have low contributions to the EXAFS signal. In our previous study, 21 we have shown that the solvation structure could hardly be detected, only on the simulated spectrum, at a distance of 4.14 Å from platinum. The solvent contribution is too low to be detected on our experimental structures.…”
Section: Fitting Proceduresmentioning
confidence: 78%
See 3 more Smart Citations
“…The remaining scattering paths have low contributions to the EXAFS signal. In our previous study, 21 we have shown that the solvation structure could hardly be detected, only on the simulated spectrum, at a distance of 4.14 Å from platinum. The solvent contribution is too low to be detected on our experimental structures.…”
Section: Fitting Proceduresmentioning
confidence: 78%
“…9,10,22,24 In this work, the solvation structure has not been included, neither in the computation of simulated spectra nor in the fitting procedure, because its contribution is really small to the EXAFS function. (CP-MD simulations show that the first shell of water molecules is at a 4.14 Å distance from platinum 20,21 ; refer also to Sec. II C).…”
Section: A Simulated Spectra and Md-based Debye-waller Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…Some of the most prominent studies include those associated with the anti-cancer drug, cisplatin. Solutions of the platinum-containing drug, cisplatin, [71] and its derivative, oxaliplatin, [72] have been analysed by bulk XAS to confirm the presence of axial water ligands. Bulk XAS has also been used for the development of controlled release drug delivery systems by confirming the integrity of drugs in the delivery agent; a specific example being the use of XAS to confirm that the structure of cisplatin did not alter following its incorporation into poly(ethylene oxide) gel.…”
Section: Platinum-containing Anti-cancer Agentsmentioning
confidence: 99%